2018
DOI: 10.1016/j.jaci.2018.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Knob protein enhances epithelial barrier integrity and attenuates airway inflammation

Abstract: Background Altered epithelial physical and functional barrier properties along with TH1/TH2 immune dysregulation are features of allergic asthma. Regulation of junction proteins to improve barrier function of airway epithelial cells has the potential for alleviation of allergic airway inflammation. Objective: We sought to determine the immunomodulatory effect of knob protein of the adenoviral capsid on allergic asthma and to investigate its mechanism of action on airway epithelial junction proteins and barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Similarly, epithelial cells exposed to mechanical compression equivalent to bronchoconstriction cause an endothelin-1 mediated increase in ASM contraction [149]. Lastly, damage to the airway epithelium is associated with an increase in inflammatory mediators, such as IL-33, which may contribute to AHR through exaggerated (eosinophilic) airway inflammation [89]. All the above mechanisms are likely especially relevant to the development of occupational asthma following inhalation of noxious molecules.…”
Section: Airway Epithelial Functionmentioning
confidence: 99%
“…Similarly, epithelial cells exposed to mechanical compression equivalent to bronchoconstriction cause an endothelin-1 mediated increase in ASM contraction [149]. Lastly, damage to the airway epithelium is associated with an increase in inflammatory mediators, such as IL-33, which may contribute to AHR through exaggerated (eosinophilic) airway inflammation [89]. All the above mechanisms are likely especially relevant to the development of occupational asthma following inhalation of noxious molecules.…”
Section: Airway Epithelial Functionmentioning
confidence: 99%
“…56 E-Cadherin plays a crucial role in adhesion junctions, which are essential for cell attachment to epithelial tissues. 57 Studies have shown that inflammatory mediators, such as cytokines 58 and proteases, 59 influence the expression and activity of E-Cadherin, resulting in increased epithelial permeability and impaired airway barrier function. In the control group, E-Cadherin was uniformly distributed like a wall across the tracheal mucosa, and the E-Cadherin barriers in the PVA and Pristine PVA group remained complete.…”
Section: Resultsmentioning
confidence: 99%
“…56 E-Cadherin plays a crucial role in adhesion junctions, which are essential for cell attachment to epithelial tissues. 57 Studies have shown that inflammatory mediators, such as cytokines 58 and proteases, 59 influence the expression and activity of E-Cadherin, resulting in increased epithelial permeability and impaired airway barrier function.…”
Section: In Vivo Evaluation Of the Biocompatibility Of Pva Tubesmentioning
confidence: 99%
“…The barrier integrity and permeability were verified based on the transepithelial electric resistance (TER) and paracellular flux. 6 Loss of PP4 reduced TER (Figure S2C) and increased paracellular flux (Figure S2D) in a concentration-dependent manner, which suggested that PP4 exerted a protective effect on epithelial barrier function by maintaining baseline expression of TJ proteins.…”
Section: Loss Of Pp4 Contributes To Diesel Exhaust Particles-induced ...mentioning
confidence: 87%